Understanding young adults' reasons for seeking 'clinically unnecessary' urgent and emergency care: A qualitative interview study - Jaqui Long; Emma Knowles; Lindsey Bishop‐Edwards; Alicia O'Cathain (Wiley, 2021)
Abstract Background Studies have identified young adults as more likely to use emergency departments for 'clinically unnecessary' problems, with limited similar evidence for emergency ambulance use. Media portrayals depict young adults as motivated by 'convenience', but little research has explored the reasons for their help‐seeking behaviour. Methods Qualitative interviews with 16 young adults (18‐30) considered by clinicians to have made unnecessary use of emergency ambulance, emergency department or an urgent GP appointment. Data analysis was informed by interpretive phenomenological analysis. Findings A number of interrelated factors contributed to participants' decisions. They were anxious about the seriousness of their symptoms, sometimes exacerbated by reduced coping capacity due to poor mental health or life stresses. They looked to others to facilitate their decision making, who sometimes encouraged urgent contact. They wanted to avoid impact on existing day‐to‐day commitments including work or study. They had strong views about different health services, sometimes based on frustration with lack of resolution of on‐going health problems. Convenience was not identified as a significant factor, although some actions could be interpreted in this light if the context was not considered. Conclusions Young adults make 'clinically unnecessary' use of urgent and emergency care for more than convenience. Their decisions need to be understood in relation to the complexity of their experience, including lack of confidence in making health‐related decisions, lowered coping capacity and concern to maintain normal daily life.